2000
DOI: 10.1128/jb.182.8.2321-2325.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Promoter Elements for the Staphylococcal Enterotoxin D Gene

Abstract: Deletion analysis of the promoter for the Staphylococcus aureus enterotoxin D determinant indicated that a 52-bp sequence, from ؊34 to ؉18, was sufficient for sed promoter function and agr regulation. A consensus ؊10 Pribnow box sequence, a less conserved ؊35 sequence, and a TG dinucleotide motif were present. Transcribed sequences (؉1 to ؉18) are essential for promoter activity.Staphylococcal food poisoning is an intoxication resulting from ingestion of foods contaminated with enterotoxin producing Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…Indeed, the agr-responsive element of sed, which encodes enterotoxin D, has recently been mapped also to within the minimal sed promoter (25). Whether the agr and autorepression targets coincide for seb remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the agr-responsive element of sed, which encodes enterotoxin D, has recently been mapped also to within the minimal sed promoter (25). Whether the agr and autorepression targets coincide for seb remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the levels of detection of SEB and SEC were genotypically and phenotypically almost identical. Furthermore, SEA is produced throughout the log phase of growth, while SEB, SEC, and SED are produced in greater quantities during the transition from the exponential to the stationary phase of growth (22). However, in accordance with the instructions of the manufacturer, SET-RPLA is performed with overnight liquid cultures, that is, cultures that are in the stationary phase.…”
Section: Discussionmentioning
confidence: 99%
“…SEA is carried on a prophage (4), and SED is carried by a plasmid (21). The gene for SEC is localized on pathogenicity islands (22). The SEB gene (entB) is also located on a chromosome (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations